The influence of battery-powered engine on the reduction of carbon dioxide production from fishing boats - Octaviani, Nilam Sari; Waskito, Dwitya Harits; Iskendar, Iskendar; Muis, Abdul; Fuadi, Noor Muhammad Ridha; Muhajirin, Muhajirin; Palebangan, Hendra; Ismoyo, Kunto; Kartikasari, Dewi; Gutami, Nanda Itohasi; Ajidarmo, Kusno (Journal of Mechatronics, Electrical Power, and Vehicular Technology, 2023)
Several technologies are currently being applied in the maritime industry to reduce greenhouse gas (GHG) emissions. An example is the implementation of an electric propulsion system with a battery charged using a renewable energy source. Meanwhile, it is important to analyze the energy demand and the quantity of emissions reduced in a vessel after installing this system. Therefore, this study focused on analyzing the energy demand and emissions produced on fishing boats, specifically the “Sandeq” fishing boats in West Sulawesi. The primary objective was to quantify the carbon dioxide emissions reduced after the conventional engine of the vessel was replaced with an electric propulsion system. Moreover, the energy demand of the boat was estimated by analyzing the daily speed, length of voyage, and engine capacity. The results showed that six batteries were required to provide the power needed for daily operation. Furthermore, the electric propulsion system was able to reduce CO2 emission by 7.94 tons annually per ship, leading to the reduction of fuel consumption and emission taxes to approximately 10 million Rupiah annually. These results were expected to encourage stakeholders to promote the transition from conventional diesel engines to electric-powered engines.